Tareas escolares y las nociones matemáticas en los niños de la Institución Educativa Inicial N° 847 Nuestra Señora de la Purísima, Punchana 2022 - Pizango Pizuri, Betty Luz (2024)
The main objective of this research was to determine the relationship between school tasks and mathematical notions in the children of the Initial Educational Institution No. 847 Nuestra Señora de la Purísima Punchana in the year 2022. To achieve this, a relational approach was used and a non-experimental design was applied with a correlational transactional method. The study population was made up of all the parents and children enrolled in the aforementioned year. The sample included all the participants, which is equivalent to a total of 118. Two techniques were used to collect data: observation and a survey. As instruments, a questionnaire and an observation guide were used, which were validated by expert review. Data analysis yielded a Rho Spearman correlation value of 0.090. Consequently, the general hypothesis was rejected, and the alternative hypothesis was accepted, which indicates that "There is no significant relationship between school tasks and mathematical notions in children of the Initial Educational Institution No. 847 Nuestra Señora de la Purísima Punchana in the year 2022".